2008
DOI: 10.1248/cpb.56.143
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating Methods for the Determination of some Anti-fungal Agents Using Densitometric and RP-HPLC Methods

Abstract: There are more than 100000 different species of fungi, many of which are beneficial to food and fermentation industries; however, hundreds are pathogenic to plants and a few hundreds have been shown to cause infection in humans. 1)Treatment of fungal infections is considerably more difficult than that of a bacterial infection as many fungal infections occur in poorly vascularised or avascular tissues. 2)Ketoconazole (KT), clotrimazole (CL), miconazole nitrate (MN) and econazole nitrate (EN) (Fig. 1) are imidaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Furthermore, literature survey reveals, MIC and HYD mixture was determined simultaneously by TLC and post column photochemical derivatization HPLC techniques [46,47] which is tedious and less applicable in quality control work. So, this work can develop quality control of miconazole and hydrocortisone in its semisolid dosage form by using simpler, available and less tedious methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, literature survey reveals, MIC and HYD mixture was determined simultaneously by TLC and post column photochemical derivatization HPLC techniques [46,47] which is tedious and less applicable in quality control work. So, this work can develop quality control of miconazole and hydrocortisone in its semisolid dosage form by using simpler, available and less tedious methods.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, several analytical methods have been reported for the determination of hydrocortisone acetate (HYD) alone or in combination with other drugs including spectrophotometry [31][32][33][34][35], and HPLC [36][37][38][39][40][41][42][43][44][45]. MIC and HYD were simultaneously determined by TLC [46] and post column photochemical derivatization HPLC [47]. Also, several analytical methods have been reported for the determination of mometasone furoate (MOM) alone or in combination with other drugs by HPLC [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…The increased efficacy, better patient compliance and good safety profile of CLZ makes it a successful therapy for curing fungal infections compared to other antifungal agents [4]. Considering the potential pharmaceutical importance of CLZ, various analytical methods have been reported for the quality control analysis of CLZ in pharmaceutical preparations, which includes titrimetry [5], high-performance liquid chromatography [6][7][8], high-performance thin layer chromatography [9,10], spectrofluorimetry [11], and derivative spectrophotometry [12,13]. The UVderivative methods lack sensitivity and possible spectral interferences could arise from inactive ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the literature revealed that several analytical methods have been reported for the determination of the studied drugs in the pure drug form, pharmaceutical dosage forms and biological samples using liquid chromatography, either in single or combined form [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], capillary zone electrophoresis methods [19], electrochemical methods [20], non-aqueous titration [2], spectrofluorimetric methods [16,21] and spectrophotometric methods [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%